RARE-13. Clinical management and functional and survival outcomes in pediatric craniopharyngioma, a patient and family perspective. (3rd June 2022) - Marshall, Emily; Cheng, Sylvia; Crowley, Julia; McCormack, Shana; Rood, Brian; Hankinson, Todd; DeCuypere, Michael; Lam, Sandy; Goldman, Stewart; Boekhoff, Svenja; Muller, Hermann L; Velasco, Ryan; et al.
Abstract: Craniopharyngiomas are rare, histologically benign, sellar/parasellar tumors with significant tumor and therapy related morbidity and impairment in quality of life (QOL). We report survey results from patients/families affected by childhood-onset craniopharyngioma to identify opportunities for improvement in management. An anonymous REDCap survey was distributed via social media and clinic visits to patients/families of craniopharyngioma survivors. Survey questions investigated perspectives on clinical management and functional and survival outcomes at initial diagnosis and recurrence. A total of 159 patients/families completed the survey, 40% (n=64) reported craniopharyngioma recurrence. For primary craniopharyngioma, maximal safe resection was the most frequent treatment reported (n=84), followed by partial resection (n=40), radiation (n=8), biopsy (n=5), and chemotherapy (n=3). Most patients (n=120) decided on a treatment plan within one week, 63 (40%) decided in one day. For recurrent craniopharyngioma, maximal safe resection and radiation were the most frequent interventions (n=33 each), followed by partial resection (n=13), chemotherapy (n=4) and biopsy (n=2). Multiple treatment options and/or participation in a clinical trial were offered to similar numbers of patients across primary and recurrent diagnoses (~21% for each). Most recurrent craniopharyngioma patients decided on management within one week (n=43). Long term effects related to tumor and treatment were identified as the primary concern in all respondents. The most common deficits for all patients were neuro-endocrine followed by vision and neurocognition problems. Neuro-endocrine complications were self-reported as the biggest impact on QOL. Families reported that they would prefer treatment options with the potential for improved QOL, even if these options also carried an increased risk of recurrence. Craniopharyngioma continues to be predominantly treated with surgery and radiation initially and with recurrence. Survivors have multiple comorbidities, with an interest in targeted therapies that preserve QOL. Novel therapies to prevent co-morbidities and provide long term benefits are necessary and upcoming.